Improvement of transfusion practice and reduction in red blood cell utilization in Belgian hospitals: Results of a national survey and benchmarking. Issue 2 (9th August 2021) - Vanden Broeck, Jana; Beeckman, Katrien; Van Gastel, Evelyne; De Keersmaecker, Luc; Devos, Timothy; Gérard, Christiane; Noens, Lucien; Putzeys, Dominique; Van Poucke, Karin; Haelterman, Margareta; Deneys, Véronique; Schots, Rik
Abstract: Background and Objectives: Belgian health authorities launched a national platform in 2011 to improve the quality of transfusion practices and blood use in Belgian hospitals. No data were available about the quality of hospital transfusion practice at the national level. Materials and Methods: Three consecutive national surveys (2012, 2014 and 2016) were performed in all 111 Belgian hospitals to assess the degree of implementation of standards in four process domains related to red blood cell (RBC) transfusion: general quality aspects, ordering of RBC, electronic traceability and reporting of adverse events. The surveys were part of a methodology based on informing, feedback and benchmarking. Responses to questions were analysed semi‐quantitatively, and hospitals could score 10 points on each of the domains. Results: The proportion of hospitals scoring below 5 per domain decreased from 16%, 70%, 14% and 11% (2012) to 2%, 17%, 1% and 1% (2016), respectively. Similarly, scores above 7.5 increased from 25%, 1%, 23% and 36% (2012) to 64%, 30%, 68% and 81% (2016), respectively. In 2016, overall quality of transfusion practices, including the four pre‐specified domains, improved continuously with an average total score (max = 40) increasing from 24.2 to 30.5 ( p = 0.0005). In addition, there was a decrease in the number of distributed and transfused RBC per 1000 population between 2011 and 2019 from 47.0 to 36.5 and 43.5 to 36.1, respectively. Conclusion: These data show that the applied methodology was a powerful tool to improve quality of transfusion practices and to optimize utilization of RBC at the national level.